2001
DOI: 10.1093/jexbot/52.363.1969
|View full text |Cite
|
Sign up to set email alerts
|

Significance of the V‐type ATPase for the adaptation to stressful growth conditions and its regulation on the molecular and biochemical level

Abstract: Two electrogenic H(+)-pumps, the vacuolar type H(+)-ATPase (V-ATPase) and the vacuolar pyrophosphatase, coexist at membranes of the secretory pathway of plants. The V-ATPase is the dominant H(+)-pump at endomembranes of most plant cells, both in terms of protein amount and, frequently, also in activity. The V-ATPase is indispensable for plant growth under normal conditions due to its role in energizing secondary transport, maintenance of solute homeostasis and, possibly, in facilitating vesicle fusion. Under s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
178
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 303 publications
(187 citation statements)
references
References 53 publications
7
178
1
1
Order By: Relevance
“…Similar nonstoichiometric changes in subunit abundance have been reported in yeast and in mammalian renal tissue, where it is thought that changes in specific subunits of the protein complex can regulate assembly and/or coupling efficiency (Valles et al, 2005;Cipriano et al, 2008), without changing the final subunit stoichiometry. In plants, noncoordinated regulation of VHA subunits in tonoplast fractions has been suggested to be important for stress tolerance (Dietz et al, 2001), although how this is achieved is not addressed. An increase in VHA-B and not VHA-A could also indicate a previously unknown, V-ATPaseindependent function for a particular VHA-B isoform, of which there are three expressed in plants (Sze et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar nonstoichiometric changes in subunit abundance have been reported in yeast and in mammalian renal tissue, where it is thought that changes in specific subunits of the protein complex can regulate assembly and/or coupling efficiency (Valles et al, 2005;Cipriano et al, 2008), without changing the final subunit stoichiometry. In plants, noncoordinated regulation of VHA subunits in tonoplast fractions has been suggested to be important for stress tolerance (Dietz et al, 2001), although how this is achieved is not addressed. An increase in VHA-B and not VHA-A could also indicate a previously unknown, V-ATPaseindependent function for a particular VHA-B isoform, of which there are three expressed in plants (Sze et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…VHA subunits A, B, C, D, E, F, G, and H make up the V 1 sector, and subunits a, b, c, d, and e compose the V o sector (Cipriano et al, 2008). In both salt-tolerant halophytes and salt-sensitive glycophytes, sodium regulates the expression at the transcript and protein levels for the tonoplast NHXs (Shi and Zhu, 2002;Yokoi et al, 2002) and different subunits of the V-ATPase Tsiantis et al, 1996;Dietz et al, 2001;Vera-Estrella et al, 2005). In addition, their transport activity has been shown to increase under salt stress (Reuveni et al, 1990;Barkla et al, 1995;Qiu et al, 2004;Vera-Estrella et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…40 The ability to respond to salinity stress with changes in the gene expression of the vacuolar ATPase might be a prerequisite and a characteristic of salt tolerance in plants. 60,61 It has been shown that the transcript levels of some subunits are upregulated in response to salt stress. In fully expanded leaves of M. crystallinum, 8 h after salt treatment, there was an increase in the transcript levels of subunit c mRNA but not of subunit A or B, 62 which correlates well with the observed increase in activity of the V-H + -ATPase in vesicles from leaf mesophyll tissue from plants treated with salt, 51 whereas in roots and young leaves, mRNA levels for all the three subunits increased about 2-fold compared to control plants.…”
Section: Regulation Of V-h + -Ppase and V-h + -Atpase Activity By Saltmentioning
confidence: 99%
“…Furthermore, Cr promotes reduction of leaf area TOLERANCE AND PROSPECTION OF PHYTOREMEDIATOR WOODY SPECIES and biochemical changes responsible for the inhibition of chlorophyll synthesis (Vajpayee et al, 1999) and disorganization of the chloroplast ultrastructure (Panda and Choudhury, 2005). Chromium stress also causes leaf chlorosis and necrosis (Barbosa et al, 2007), oxidative damages in biomolecules such as lipids and proteins (Vajpayee et al, 2002), disturbances in mineral nutrition (Barbosa et al, 2007), increase in glutathione and ascorbic acid production (Shanker, 2003), alterations in the metabolic pool that intermediates the production of phytochelatins and histidine, interference in the activity of nitrate reductase (Panda and Patra, 2000), root Fe 3+ reductase (Shanker et al, 2004), plasma membrane H + -ATPase (Dietz et al, 2001), Na 2+ /K + -dependent ATPase (Pauls et al, 1980), Ca 2+ -dependent ATPase (Serpersu et al, 1982), alkaline phosphatases (Viola et al, 1980), superoxide dismutase, catalase and peroxidase (Samantaray et al, 2001) and, eventually, plant growth reduction, hindering its development and, finally, being able to cause its death ( Barbosa et al, 2007).…”
Section: Coppermentioning
confidence: 99%